Planning, Designing, Building, and Moving a Large Volume Maternity Service to a New Labor and Birth Unit. Issue 6 (November 2016) - Thompson, Heather; Legorreta, Kimberly; Maher, Mary Ann; Lavin, Melanie M.
Abstract: Background: Our health system recognized the need to update facility space and associated technology for the labor and birth unit within our large volume perinatal service to improve the patient experience, and enhance safety, quality of care, and staff satisfaction. When an organization decides to invest 30 million dollars in a construction project such as a new labor and birth unit, many factors and considerations are involved. Financial support, planning, design, and construction phases of building a new unit are complex and therefore require strong interdisciplinary collaboration, leadership, and project management. Methods: The new labor and birth unit required nearly 3 years of planning, designing, and construction. Patient and family preferences were elicited through consumer focus groups. Multiple meetings with the administrative and nursing leadership teams, staff nurses, nurse midwives, and physicians were held to generate ideas for improvement in the new space. Involving frontline clinicians and childbearing women in the process was critical to success. The labor and birth unit moved to a new patient tower in a space that was doubled in square footage and geographically now on three separate floors. In the 6 months prior to the move, many efforts were made in our community to share our new space. The marketing strategy was very detailed and creative with ongoing input from the nursing leadership team. The nursing staff was involved in every step along the way. It was critical to have champions as workflow teams emerged. We hosted simulation drills and tested scenarios with new workflows. Move day was rehearsed with representatives of all members of the perinatal team participating. Results: These efforts ultimately resulted in a move time of 5 hours. Birth volumes increased 7% within the first 6 months. After 3 years in our new space, our birth volumes have risen nearly 15% and are still growing. Clinical Implications: Key processes and roles responsible for a successful build, efficient and safe move day, and optimal operational utility, as anticipated, of a new labor and birth unit in a large volume perinatal service are detailed. Abstract : There are many important aspects in the process of planning, designing, building, and moving a large volume maternity service to a new labor and birth unit. Nurses play a crucial role in making sure patient safety and quality care are at the forefront of the project. The data presented here will be useful to other teams planning a new labor and birth unit.